Characterization of the ethanol-triglyceride transesterification reaction under counter current flow system - Chong, Ee Rong (2014)
Biodiesel is a mono-alkyl ester of vegetable oil, animal fat and recycled cooking oil. It has been recognized worldwide as an alternative source to replace the known petroleum reserves that are limited and eventually run out as to many aspects to be concerned like environmental and sustainability issues. It is commonly prepared by transesterification of triglycerides or the esterification of free fatty acid with methanol or ethanol by stirring and accelerated by the presence of base or acidic catalyst. In this study, palm oil transesterification reaction with ethanol will be conducted with a set of cooking oilabsolute ethanol ratios under the counter current flow system by using the extractive reactor column so that the data obtained can be used to investigate the behaviour of the reacting fluid that flows counter currently with the reactant so lvent. Different composition of the cooking oil and absolute ethanol were mixed and observed using viscometer under different RPM. Torque, viscosity, shear strength and shear stress were observed, recorded and plotted in figure 3, figure 4, figure 5 and figure 6. The torque was decreasing when the ratio of the cooking was decreasing. For RPM 50, torque of ratio (cooking oil:absolute ethanol) 8:1 was 8.3% decreasing to 0.2% when the ratio was (cooking oil:absolute ethanol) 1:8. The viscosity was decreasing when the ratio of cooking oil decreasing as well. For RPM 50, viscosity of ratio (cooking oil:absolute ethanol) 8:1 was 50.4 mPaS decreasing to 1.8 mPas when the ratio was (cooking oil:absolute ethanol) 1:8. The shear strength was decreasing as well when the ratio of cooking was decreasing. For RPM 50, shear strength of ratio (cooking oil:absolute ethanol) 8:1 was 0.85 N/m² decreasing to 0.02 N/m² when the ratio was (cooking oil:absolute ethanol) 1:8. However, the shear rate of each ratio of reactant mixture had no changes when the ratio was changing. Unfortunately, the extractive reactor column had some problems when the experiment was carried out. No data can be obtained from the experiment. From the observation, few phenomena can be seen through the photos. The white colour fatty acid that was formed after 1 day. Besides, figure 9 shown that the corroded flow meter by absolute ethanol which contained KOH. In figure 10, the broken flow meter which affect the research hardly to continue